Baseline laboratory parameters predicting clinical outcome in melanoma patients treated with ipilimumab: a single‐centre analysis. (22nd November 2017) - Gambichler, T.; Brown, V.; Steuke, A.‐K.; Schmitz, L.; Stockfleth, E.; Susok, L.
Abstract: Background: Overall response rates (ORRs) for ipilimumab in advanced melanoma are only about 10%. Hence, it is important to explore biomarkers predicting ipilimumab responders. Objective: We aimed to explore biomarkers to predict therapy outcome in melanoma patients who have undergone standard ipilimumab therapy in a real‐world setting. Methods: Databases of cutaneous melanoma patients ( n  = 52) who had received ipilimumab were reviewed and data collected on patient characteristics and diverse laboratory parameters. We performed univariate and multivariate statistics including logistic regression analysis and Cox proportional‐hazards regression. Results: Baseline leucocytes, lymphocytes, eosinophils, thrombocytes, neutrophil/lymphocyte ratio, thrombocytes/lymphocyte ratio, eosinophil/lymphocyte ratio and serum vitamin D levels were not significantly associated with ORR, progression‐free survival (PFS) and melanoma‐specific survival (MSS). Multivariate analysis confirmed anti‐PD‐1 pretreatment as significant predictor for ORR following ipilimumab therapy. Low‐LDH levels and more than two ipilimumab cycles turned out to be significant independent predictors for prolonged PFS. Low‐S100B levels and anti‐PD‐1 treatment before or after ipilimumab were significant independent predictors for improved MSS. All aforementioned parameters and faecal calprotectin did not turn out to be predictors for ipilimumab‐induced autoimmune‐related adverse events and autoimmune colitis, respectively. Conclusions: Low serum LDH before ipilimumab treatment is an independent predictor for improved PFS. Furthermore, low serum S100B is an independent predictor for MSS. The number of ipilimumab cycles (>2) is significantly associated with prolonged PFS. Pretreatment calprotectin does not predict the occurrence of autoimmune colitis under ipilimumab therapy.